THE IDENTIFICATION OF PERSUASIVE MESSAGE CAMPAIGN “WONDERFUL INDONESIA 2015” - Ilona Vicenovie Oisina; Angelia Sulistiwaty Sugianto (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2017)
Tourism nowadays is entering a new era.  Recent years, tourism is the best bussiness in many countries. This research discusses about The branding strategy analyzed using STP theory (Segmentation, Targeting and Positioning) on Wonderful Indonesia campaign. This campaign is the Leading Campaign for Indonesia tourism in International level. Data collection was obtained from observation, books and interview. The result obtained from STP analysis theory can be used to develop branding strategy in wonderful indonesia campaign. The innovation is founded in tourism and  development of tourism product like village and religion tourism can be applied in Indonesia tourism. Within positive development in this campaign, Indonesia is expected able to compete with the other ASEAN countries while AFTA and MEA policy applied in 2015.